Multicriteria and multiobjective models for risk. (2015) - Almeida, Adiel Teixeira de; Cavalcante, Cristiano; Alencar, Marcelo Hazin; Ferreira, Rodrigo José Pires; Almeida-Filho, Adiel Teixeira de; Garcez, Thalles Vitelli
No abstract available